2020
DOI: 10.1002/ijc.33400
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial barriers to healthcare access for breast cancer diagnosis in sub‐Saharan African settings: The African Breast Cancer—Disparities in Outcomes Cohort Study

Abstract: We examined the geospatial dimension of delays to diagnosis of breast cancer in a prospective study of 1541 women newly diagnosed in the African Breast Cancer—Disparities in Outcomes (ABC‐DO) Study. Women were recruited at cancer treatment facilities in Namibia, Nigeria, Uganda and Zambia. The baseline interview included information used to generate the geospatial features: urban/rural residence, travel mode to treatment facility and straight‐line distances from home to first‐care provider and to diagnostic/tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 23 publications
(59 reference statements)
3
38
0
Order By: Relevance
“…This finding could be explained by the fact that patients from rural areas are farther away from diagnostic healthcare facilities and have low levels of information about breast cancer and transportation access; as a result, they present after the disease is advanced and metastasised. This result is in line with a study carried out in sub-Saharan Africa in which distance to the diagnostic/treatment facility is a problem in most African countries [43].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding could be explained by the fact that patients from rural areas are farther away from diagnostic healthcare facilities and have low levels of information about breast cancer and transportation access; as a result, they present after the disease is advanced and metastasised. This result is in line with a study carried out in sub-Saharan Africa in which distance to the diagnostic/treatment facility is a problem in most African countries [43].…”
Section: Discussionsupporting
confidence: 91%
“…Distance to the nearby healthcare facility ≥5 km was also associated with late presentation of patients with breast cancer. Women living in the rural areas presented with advanced metastatic disease than women living in urban areas in Sudan and sub-Saharan Africa [ 42 , 43 ]. This might be due to the long distance travelling to cancer diagnostic centres as well as the difficulty of getting information access about breast cancer to understand the early symptoms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The African Breast Cancer Disparities in Outcomes Cohort Study Open identified that distance to a diagnostic health facility was independently associated with a delay in diagnosis of greater than 3 months and late diagnosis (stage III/ IV) for women with breast cancer in Namibia, Uganda and Zambia. 37 In Ethiopia, rural residence and a distance greater than 5 km from a cancer referral centre were associated with a delay greater than 3 months between onset of symptoms and medical consultation. 38 Lastly, a diagnostic hospital in South Africa identified that their patients who lived farther from the hospital were more likely to have late stage (stage III/IV) breast cancer at time of diagnosis.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, a higher breast cancer stage at diagnosis was the most important determinant of self-reporting an ASP. In contrast to HICs where most women have an early stage diagnosis, late stage diagnosis for breast cancer is common in SSA due to low breast cancer awareness among both women and healthcare professionals, and long delays to presentation of symptomatic women to a healthcare provider, final diagnosis and treatment initiation, with disadvantaged populations being particularly affected [ 11 , 12 , 22 , 23 ]. In our cohort, three quarters of women had a late stage breast cancer at diagnosis, with nearly half having a tumour size over five centimetres and about two thirds positive lymph nodes at diagnosis.…”
Section: Discussionmentioning
confidence: 99%